Dhikr Assemblies in Urban Palembang: Continuity of Malay Islamic Tradition and Socio-Religious Adaptation - Hidayah HT; Abdullah Idi; Muhammad Noupal; Pathur Rahman; Nurseri Hasanah; Ahamakosee Kasor (Bulletin of Community Engagement, 2026)
This study aims to analyze the dynamics of the 21st-century dhikr assembly in the city of Palembang, particularly changes in construction, the expansion of social roles, and the factors driving its transformation within the lives of Muslim urban communities. This study uses a qualitative approach with a phenomenological-sociological-based field study design. Data were collected through semi-structured interviews, observations, and documentation in May–June 2025, involving dhikr assembly supervisors, active congregations, religious leaders, community leaders, government officials, and social actors involved in assembly activities. The data were analyzed using thematic analysis through the stages of transcription, repeated reading, initial coding, categorization, theme structuring, interpretation, and conclusion drawn. The results of the study show that the dhikr assembly in Palembang has transformed from a ritual-spiritual space into a dynamic, adaptive, and multifunctional urban socio-religious institution. The transformation can be seen in changes in the role of the guide, variations in dhikr readings, more communicative processions, heterogeneous congregations, expansion of activity venues, use of digital media, and the development of social, economic, recreative, and public programs. This research also found that the dhikr assembly maintains the Malay Islamic tradition through ratib, sanad, guidebooks, assembly manners, verses, hadrah, haul, and pilgrimage, while adapting to the needs of urban communities through social activities, youth involvement, informal economic activities, spiritual tourism, and digital da’wah. This study concludes that the dhikr assembly in Palembang represents a pattern of continuity and change, serving as a space for spiritual adaptation, the preservation of local Islamic traditions, and the social negotiation among urban Muslim communities.